Exostosin-1/exostosin-2 expression and favorable kidney outcomes in lupus nephritis: a retrospective cohort study - Zavala-Miranda, Maria Fernanda; Sobrino-Vargas, Ana María; Hernández-Andrade, Adriana; Caballero-Malacara, Valeria; Pérez-Arias, Abril A.; Márquez-Macedo, Sofía E.; Nordmann-Gomes, Alberto; Navarro-Sánchez, Valeria; Juárez-Cuevas, Bernardo; Uribe-Uribe, Norma O.; Mejia-Vilet, Juan M. (Clinical rheumatology, 2024)
Introduction/Objectives The heterodimer exostosin-1/exostosin-2 (EXO-1/2) is a novel antigen observed in membranous nephropathy associated with systemic lupus erythematosus. This study aimed to evaluate the association between EXO-1/2 positivity in kidney biopsy and kidney outcomes. Methods The kidney biopsy tissue from 50 class 5 lupus nephritis (LN) and 55 mixed class 3/4 + 5 LN patients was stained for EXO-1/2. Baseline clinical and histological characteristics were compared between EXO-1/2 positive and EXO-1/2 negative patients. Time-to-event analyses were performed to compare rates of response to therapy, kidney flares, and progression to a 40% decline of the glomerular filtration rate (eGFR), doubling of serum creatinine, and kidney failure. Results Fourteen out of 50 (28%) of class 5 and 5 out of 55 (9%) of mixed class 3/4 + 5 LN stained positive for EXO-1/2. Patients with class 5 LN and EXO-1/2 positive stain were younger, with better kidney function at presentation, and lower scarring in the kidney biopsy analysis. Over a median follow-up of 100 months, patients with positive EXO-1/2 staining had significantly lower rates of progression in the full cohort. When analyzed separately in class 5 and mixed class LN subgroups, there were significantly lower rates of progression to a 40% decline of the eGFR and non-statistically significant trends for doubling of serum creatinine and kidney failure. Conclusion EXO-1/2 is a novel antigen detected in class 5 LN and associated with a good prognosis of kidney function. The incorporation of EXO-1/2 staining in clinical practice can potentially modify the management of LN due to its prognostic implications. Key Points • Exostosin-1/exostosin-2 antigen has been found in cases of membranous nephropathy associated with autoimmune diseases such as systemic lupus erythematosus. • Exostosin-1/exostosin-2 staining in the kidney biopsy of class 5 or mixed class 3/4 + 5 lupus nephritis is associated with a good long-term prognosis of kidney function. • The incorporation of exostosin-1/exostosin-2 staining into clinical practice can potentially modify management due to its prognostic implications.